Insuficiência de vitamina D em pacientes infectados pelo HIV tratados com terapia antirretroviral contendo tenofovir - Maria, Jéssika Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Vitamin D is an essential nutrient for the mineralization of the skeleton and maintenance of bone mass. Recent evidence has shown a high prevalence of vitamin D deficiency in HIV-infected, mainly in use of tenofovir (TDF), to affect the renal tubular cells, causing the loss of electrolyte and reduced bone mass. Objective: To evaluate the effects of tenofovir in serum levels of vitamin D and its impact on bone mineral density by comparing patients on tenofovir system versus non tenofovir. Methods: Cross-sectional study with 127 individuals of both genders, aged between 18 and 60 years. Participants were divided into the following 3 groups: group using tenofovir (GTDF+): n = 48 participants, group not using tenofovir (GTDF-): n = 49 participants and control group (CG): n = 30 participants seronegative for HIV. Dual energy x-ray absorptiometry (DXA) was performed to evaluate bone mineral density (BMD) and body composition. Peripheral blood samples were collected for the determination of 25-hydroxyvitamin D (25(OH)D), parathyroid hormone (PTH), luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone, estradiol, creatinine, urea, albumin, calcium, magnesium and phosphorus. The glomerular filtration rate was calculated and the dietary intake evaluated. Results: Vitamin D had insufficient serum levels in all study groups as shown inadequate dietary intake. The GTDF + group showed lower serum levels of vitamin D when viewed with the values of GTDF- group, and 31% of patients using TDF showed serum deficiency. It was observed that up to 25% of the participants use of tenofovir showed osteopenia, especially in the lumbar spine bone site, whereas the group without tenofovir was higher percentage for osteoporosis. Conclusion: Most of the participants infected with HIV under control or not of tenofovir had insufficient vitamin D deficient levels ...

Introdução: A vitamina D é um nutriente essencial para a mineralização do esqueleto e manutenção de massa óssea. Evidências recentes têm demonstrado uma alta prevalência de deficiência de vitamina D em infectados pelo HIV, principalmente em uso de tenofovir (TDF), por afetar as células tubulares renais, causando a perda de eletrólito e a redução da massa óssea. Objetivo: avaliar os efeitos do tenofovir nos níveis séricos de vitamina D e seu impacto sobre a densidade mineral óssea em pacientes sob regime de tenofovir ou não. Metodologia: Estudo transversal com 127 indivíduos, de ambos os sexos, com idades entre 18 e 60 anos. Os participantes foram subdivididos em 3 grupos, sendo: grupo em uso do tenofovir (GTDF+): n= 48 participantes, grupo sem uso de tenofovir (GTDF-): n= 49 participantes e grupo controle (GC): n= 30 participantes soronegativos para HIV. Realizou-se dual energy x-ray absorptiometry (DXA) para avaliação da densidade mineral óssea (DMO) e composição corporal. Amostras de sangue periférico foram coletadas para determinações da 25 hidroxivitamina D (25(OH)D), hormônio da paratireoide (PTH), hormônio luteinizante (LH), hormônio folículo estimulante (FSH), testosterona, estradiol, creatinina, uréia, albumina, cálcio, magnésio e fósforo. Calculou-se a taxa de filtração glomerular e avaliação do consumo alimentar. Resultados: A vitamina D sérica apresentou valores insuficientes na maioria dos participantes e o consumo alimentar de vitamina D, cálcio e magnésio mostraram abaixo da recomendação dietética em todos os grupos do estudo. O GTDF+ apresentou valores séricos menores de vitamina D quando observado com os valores do grupo GTDF-. A deficiência de vitamina D foi observada em 31% dos pacientes em uso de TDF e em 20% dos pacientes sem uso de tenofovir. Observou-se que até 25% dos participantes em uso de tenofovir...
Keywords: Vitamina D; Ossos - Doenças; Sangue - Analise e quimica; Hormonios; Creatinina; Estradiol; Ureia; Vitamin D